Structural Equation Model of the Influence of Customer Relationship Management and Customer Experience Management on Brand Loyalty: The Role of Customer Engagement in the Context of Coffee Shops at Gas Stations - Srathongkham, Tarika; Supasettaysa, Gumporn (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
This research aimed to achieve two objectives: (1) examine customer relationship management, customer experience management, customer engagement, and brand loyalty; (2) develop a causal model of factors influencing brand loyalty; (3) investigate the direct and indirect effects of these factors; and (4) propose strategic recommendations for enhancing coffee shop services in petrol stations to foster sustainable brand loyalty. The sample consisted of 600 customers selected through purposive sampling, targeting those with direct service experience, combined with quota sampling to ensure adequate distribution across locations and service times. As a non-probability approach was employed, the results cannot be generalized to the entire population but provide meaningful insights into the defined group and the research context. Data were collected using a structured questionnaire, and statistical analyses included descriptive statistics and structural equation modeling (SEM). The findings revealed that the proposed model demonstrated a good fit with the empirical data (X² = 33.509, df = 22, X²/df = 1.523, CFI = 0.998, RMSEA = 0.030). Customer relationship management, customer experience management, and customer engagement exerted direct effects on brand loyalty, while customer relationship management and customer experience management also directly influenced customer engagement and indirectly affected brand loyalty. Overall, all variables scored high mean values, reflecting positive perceptions among respondents. The study recommends strategies centered on enhancing customer engagement through meaningful experience design, personalized relationship building, and leveraging customer insights to guide service strategies in petrol station coffee shops. These findings contribute to the understanding of how integrated relationship and experience management can strengthen sustainable and distinctive brand loyalty. Article history: Received 27 April 2025 Revised 20 September 2025 Accepted 24 September 2025 SIMILARITY INDEX = 4.19 %